Perhitungan Unit Cost Pengembangan Sistem Informasi Pondok Pesantren Dengan Metode ABC (Activity Based Costing) - Yaqin, Muhammad Ainul; Wicaksono, Muhammad Bagus; Falahian, Derida Elfraim; Hakim, Eryan Rachman (STIKOM Tunas Bangsa Pematangsiantar, 2020)
The purpose of this study is to describe and calculate the unit cost in developing the information system for Islamic boarding schools. This research uses a descriptive-quantitative approach. Data collection methods are observation and documentation. The descriptive approach in this study is used to analyze and interpret the data from observations and documentation that have been collected, while the quantitative approach in this study is used to explain the nominal unit cost calculation using the ABC (Activity Based Costing) method. In every development of an information system, the costs required are quite a lot and have several complex parameters, so that one of the management concepts is needed, namely cost accuracy. This becomes important for users of cost information to determine the cost effectiveness used by each unit as well as a reference price in further information system development, in this case the cost of developing an information system for Islamic boarding schools. The method we use in calculating unit costs is ABC (Activity Based Costing), where the calculation system charges costs for each activity involved before calculating product costs. The number of activities in developing a software or information system makes this method suitable to be applied in cost accuracy. The standard benchmark for the cost of procuring goods and services in this study is in accordance with government regulations and several observations, while the amount of salary costs follows the 2019 Minimum Standard Guidelines issued by INKINDO (National Association of Indonesian Consultants). The results of this study show that in developing the information system for Islamic boarding schools, the total cost required is Rp. 79,100,000.00 with a unit cost of Rp. 17,673,607.35.